Ursolic acid potentializes conventional therapy in experimental leishmaniasis - Jesus, Jéssica Adriana; Da Silva, Thays Nicolli Fragoso; Yamamoto, Eduardo Seiji; Lago, João Henrique G.; Laurenti, Márcia Dalastra; Passero, Luiz Felipe Domingues [UNESP] (MDPI, 2020)
Ursolic acid (UA) is a triterpene with a broad array of pharmacological activities. In leishmaniasis, UA killed different species of parasites, and it was active in the experimental model of cutaneous and visceral leishmaniasis. Thus, the objective of this work was to study the therapeutic efficacy of the conventional drugs amphotericin B (AmB) or glucantime (Glu) combined with UA in experimental visceral and cutaneous leishmaniasis, respectively. L. (L.) infantuminfected hamsters were treated with AmB alone or combined with UA. L. (L.) amazonensis-infected BALB/c mice were treated with Glu alone or combined with UA. Animals were treated for 15 consecutive days by intraperitoneal or intralesional routes. Following one week after the last dose, the tissue parasitism and cellular immune responses were analyzed. Hamsters treated with 0.2 and 1.0 mg/kg of AmB plus 1.0 mg/kg of UA showed low hepatic and splenic parasitisms; however, AmB given as monotherapy did not reduce the number of viable parasites in the spleen of treated animals. In cutaneous leishmaniasis, Glu given as monotherapy was inactive at 2.0 mg/kg, showed mild activity at 10.0 mg/kg, and at 50.0 mg/kg was highly active at eliminating parasites in the skin. When animals were treated with Glu plus UA, higher leishmanicidal activity was observed in comparison to all groups treated with monotherapy schemes, and such activity was related to lesion improvement and upregulation of IFN-γ production. Altogether, data suggest that the association of drugs for the treatment of leishmaniasis can increase the efficiency of the treatment and decreasethe toxicity associated to the conventional drugs.
Keywords: Amphotericin B; Cutaneous leishmaniasis; Glucantime; Leishmaniasis; Therapy; Visceral leishmaniasis